Effectiveness of crack sealing in reducing the rate of pavement deterioration. Issue 1 (9th November 2018) - Alabi, Bortiorkor Nii Tsui; Keller, Julius
Abstract : Cracks in highway and airfield pavements pose safety challenges because they can lead to serious surface defects that impair the operations of aircraft or automobiles that use these pavements. It is therefore important to apply treatments that reduce the rate of deterioration caused by cracking. This paper presents a model for determining the effectiveness of crack sealing in terms of the reduction in the rate of pavement deterioration. The model utilises a functional form that accounts for the pre-sealing level of deterioration and the effort (maintenance dollars) expended on the crack sealing treatment, thus facilitating a more intuitive engineering interpretation of the model formulation. Linear and non-linear regression techniques were used to estimate the model coefficients. Using sensitivity analysis, the model quantified the extent to which the level of pre-sealing pavement condition and maintenance treatment expenditure influence the effectiveness (reduction in the rate of deterioration) of the sealing treatment. The paper also shows that the sealing effectiveness due to the crack sealing treatment does not exceed a certain limit (cap) and that this cap is a function of the pre-sealing pavement condition. Furthermore, the paper's results suggest that the consequences of deferring or not carrying out sealing of a cracked pavement depend on the pre-treatment pavement condition.